2011
DOI: 10.1097/prs.0b013e318230c5d0
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman Primate Model of Fibula Vascularized Composite Tissue Allotransplantation Demonstrates Donor-Recipient Bony Union

Abstract: In contrast to successes in extremity vascularized composite tissue allotransplantation, the authors' nonhuman primate fibular vascularized composite tissue allotransplantation model showed early skin loss, replacement of donor bone marrow, and chronic rejection. Donor-recipient bone union did occur and supports the potential for reconstruction of bony continuity defects using isolated vascularized bone allotransplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Notably, a recent experimental report in nonhuman primates found that BM of a vascularized fibula allograft was completely substituted by recipient cells, and then its facilitating properties for tolerance may be abolished after 6 months. 70 Acute rejection has been identified as a risk factor for graft loss caused by CR after KAT (odds ratio, 7.45, P = 0.01). 6 However, it was not possible to assess this for HAT because there was only 1 graft loss caused by CR.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, a recent experimental report in nonhuman primates found that BM of a vascularized fibula allograft was completely substituted by recipient cells, and then its facilitating properties for tolerance may be abolished after 6 months. 70 Acute rejection has been identified as a risk factor for graft loss caused by CR after KAT (odds ratio, 7.45, P = 0.01). 6 However, it was not possible to assess this for HAT because there was only 1 graft loss caused by CR.…”
Section: Discussionmentioning
confidence: 97%
“…10 No adjunct induction therapies or corticosteroids were administered, and rejection episodes were not treated with additional therapies to follow the natural clinical course of allograft survival. 8,11 Serial graft biopsies were performed and evaluated by a transplant pathologist as previously described. 5 Immunosuppression was withdrawn in the absence of acute rejection in those animals with graft survival greater than 200 days to evaluate for graft tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…12 Chronic rejection or chronic allograft vasculopathy have not been reported; these disorders were previously considered possible and have become evident in human hand transplantation 44 and preclinical studies. 45 Hyperacute rejection from pre-formed antibodies has also not been reported. Donor-derived macrochimerism has not been reported.…”
Section: Immunological Outcomesmentioning
confidence: 99%